Making Dalmatia green again: reforestation at the 'horrible edge' of Empire 1870–1918. (2nd January 2021) - Tekić, Ivan; Watkins, Charles
ABSTRACT: Reforestation has been one of the main forestry activities in the karst terrain of Dalmatia, Croatia, for more than a century. This paper examines the history behind reforestation schemes in Dalmatia, a kingdom at the periphery of the Austro-Hungarian Empire. It explores how the ideas of Austrian foresters, based at the centre of Empire, were transmitted and put into practice. Late nineteenth-century forestry debates in contemporary forestry texts and the Šumarski list, the forestry journal published since 1877, are analysed and different narratives concerning the lack of woodland explored. The paper goes on to examine how reforestation of the karst was carried out in the region around Šibenik making use of local archives, historical maps, cadastral surveys, and photographs. Disputes between foresters and local villagers who wished to protect their grazing rights are uncovered and a link between the development of tourism and the selection of sites to be reforested is identified.